Submarine groundwater discharge: An Asian overview. (June 2023) - Sajeev, Sruthy; Muthukumar, P.; Selvam, S.
Abstract: Submarine groundwater discharge (SGD) is the combination of fresh and saline groundwater flux to marine system through continental boundaries regardless of its chemical composition and factors influencing the flow. We have discussed the SGD studies in the Asian context; SGD has been studied in various parts of Asia, including China, Japan, South Korea, and Southeast Asia. In China, SGD has been studied in several coastal regions, including the Yellow Sea, the East China Sea, and the South China Sea. In Japan, SGD has been studied in the Pacific coast, where it has been found to be an important source of fresh water to the coastal ocean. In South Korea, SGD has been studied in the Yellow Sea, where it has been found to be an important source of fresh water to the coastal ocean. In Southeast Asia, SGD has been studied in several countries, including Thailand, Vietnam, and Indonesia. Recently the SGD studies acquired much development India, the research on SGD in India is limited, and more studies are needed to understand the SGD process, its impact on the coastal environment, and the management strategies, Groundwater extraction for irrigation, industry, and domestic use is increasing in India, which can affect the SGD process in coastal aquifers. Overall, the studies suggest that SGD is an important process in Asian coastal regions, playing a role in the supply of fresh water and the transport of pollutants and nutrients. Graphical abstract: Image 1 Highlights: SGD studies have concentrated in Japan, Korea, India, China, Thailand and Bangladesh. The SGD can be represented as the sum of SGDF and SGDR . The estimation of SGD fluxes into the coastal systems can be accomplished by many forces. SGD supports the primary production in the coastal waters.